2020
DOI: 10.1073/pnas.2016954117
|View full text |Cite
|
Sign up to set email alerts
|

Normal levels of ribosome-associated chaperones cure two groups of [PSI+] prion variants

Abstract: The yeast prion [PSI+] is a self-propagating amyloid of the translation termination factor, Sup35p. For known pathogenic prions, such as [PSI+], a single protein can form an array of different amyloid structures (prion variants) each stably inherited and with differing biological properties. The ribosome-associated chaperones, Ssb1/2p (Hsp70s), and RAC (Zuo1p (Hsp40) and Ssz1p (Hsp70)), enhance de novo protein folding by protecting nascent polypeptide chains from misfolding and maintain translational fidelity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 81 publications
4
26
0
Order By: Relevance
“…A series of studies by the Wickner lab and coauthors showed that the absence or reduced activity of several proteins allow the appearance of [ PSI +] variants that are unable to propagate in the wild-type background. These proteins are ribosome-associated Hsp70 Ssb1 and Ssb2 [ 82 ], Hsp104 weakened by T160M mutation [ 83 ], Upf1,2,3 nonsense-mediated mRNA decay factors [ 84 ] and Siw14 pyrophosphatase [ 85 ]. For the [ URE3 ] prion, nearly all isolates appearing in the ∆btn2∆cur1 double mutant were unable to propagate in the wild-type background [ 86 , 87 ].…”
Section: [ Psi +] Variantsmentioning
confidence: 99%
“…A series of studies by the Wickner lab and coauthors showed that the absence or reduced activity of several proteins allow the appearance of [ PSI +] variants that are unable to propagate in the wild-type background. These proteins are ribosome-associated Hsp70 Ssb1 and Ssb2 [ 82 ], Hsp104 weakened by T160M mutation [ 83 ], Upf1,2,3 nonsense-mediated mRNA decay factors [ 84 ] and Siw14 pyrophosphatase [ 85 ]. For the [ URE3 ] prion, nearly all isolates appearing in the ∆btn2∆cur1 double mutant were unable to propagate in the wild-type background [ 86 , 87 ].…”
Section: [ Psi +] Variantsmentioning
confidence: 99%
“…We have confirmed the earlier work on ribosome-associated chaperones, but in addition to the increased frequency of [PSI+], we found that more than half of the [PSI+] variants isolated in any of the ssb1/2 Δ, zuo1 Δ or ssz1 Δ mutants are lost upon replacement of the corresponding w.t. gene, indicating that these genes block propagation of most [PSI+] variants arising [ 72 ]. The mechanism of the anti-prion effect likely involves their known role in facilitating proper folding of the normal protein, but this mechanism would suggest that they might likewise affect formation of any prion, and we were unable to detect any effect on [URE3] [ 72 ].…”
Section: Ribosome-associated Chaperones Cure Many [Psi+] Variants And...mentioning
confidence: 99%
“…gene, indicating that these genes block propagation of most [PSI+] variants arising [ 72 ]. The mechanism of the anti-prion effect likely involves their known role in facilitating proper folding of the normal protein, but this mechanism would suggest that they might likewise affect formation of any prion, and we were unable to detect any effect on [URE3] [ 72 ]. The proximity of the ribosome-associated chaperones to Sup35, and the small—but real—effect of their mutants on translation termination efficiency, makes possible a direct effect on the mature Sup35.…”
Section: Ribosome-associated Chaperones Cure Many [Psi+] Variants And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fitness defects caused by prions range from moderate stress to lethality [ 20 , 21 , 22 , 23 , 24 ]. Several independent PQC systems of yeast, which protect cells from a broad range of harmful protein misfolding problems, also counteract prion toxicity and the ability of prions to become established or to propagate [ 21 , 22 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Prions that arise de novo when a component of one of these systems is missing are almost entirely eliminated when it is restored, which shows that most prions that could arise are being eliminated by these cellular anti-prion activities.…”
Section: Introductionmentioning
confidence: 99%